“Management of radicular cyst in the aesthetic zone mimicking periapical pathology: a diagnostic challenge" - Shahin, Ibtisam; Tandon , Sapna; Kumari , Payal; Sharma, Sonika; Chauhan, Himanshu; Chauhan, Himanshu; Mehra, Hemant (Journal of Neonatal Surgery, 2025)
Background:Radicular cysts are the most common inflammatory odontogenic cysts, typically arising from non-vital teeth. Though frequently asymptomatic and discovered incidentally, their presentation in the anterior maxilla — an aesthetically sensitive region — may mimic other periapical pathologies, posing diagnostic and therapeutic challenges. Case Presentation:A 46-year-old male presented with pus discharge and swelling in the anterior maxillary region. Clinical examination revealed a non-fluctuant, non-tender lesion with a sinus tract in relation to teeth 21–23, which were non-vital. Fine Needle Aspiration yielded yellowish, blood-tinged fluid, suggestive of a secondary infection. Radiographic and CBCT imaging revealed an ill-defined periapical radiolucency with cortical perforation extending from tooth 21 to 23. Root canal treatment of the affected teeth was performed, followed by surgical enucleation of the lesion and apicoectomy under local anaesthesia. Histopathologic analysis confirmed the diagnosis of a radicular cyst. Conclusion:This case highlights the importance of integrating clinical, radiographic, and histopathological findings in diagnosing periapical lesions, especially in cosmetically sensitive zones. A combined endodontic and surgical approach proved to be effective in achieving complete resolution with minimal morbidity and optimal aesthetic preservation.. Keywords: Radicular cyst, Periapical cyst, Root end cyst, Inflammatory odontogenic cyst, Anterior maxilla, Periapical